The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1208/pt060115
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of NIR spectroscopy for nondestructive analysis of physical and chemical attributes of sulfamethazine bolus dosage forms

Abstract: The goal of this study was to assess the utility of near infrared (NIR) spectroscopy for the determination of content uniformity, tablet crushing strength (tablet hardness), and dissolution rate in sulfamethazine veterinary bolus dosage forms. A formulation containing sulfamethazine, corn starch, and magnesium stearate was employed. The formulations were wet granulated with a 10% (wt/vol) starch paste in a high shear granulator and dried at 60 degrees C in a convection tray dryer. The tablets were compressed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…The content uniformity dataset also showed the highest correlation coefficients and lowest SEC and SEP values. Therefore, it appears that NIRS is superior at predicting chemical properties (e.g., CU) over physical (e.g., compression force or crushing force); these findings are consistent with other research (22). A paired t test showed that there was no significant difference (p>0.05) between the laboratory results and predicted NIR values for content uniformity of theophylline tablets (p=0.44).…”
Section: Content Uniformity Models-regression Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…The content uniformity dataset also showed the highest correlation coefficients and lowest SEC and SEP values. Therefore, it appears that NIRS is superior at predicting chemical properties (e.g., CU) over physical (e.g., compression force or crushing force); these findings are consistent with other research (22). A paired t test showed that there was no significant difference (p>0.05) between the laboratory results and predicted NIR values for content uniformity of theophylline tablets (p=0.44).…”
Section: Content Uniformity Models-regression Analysissupporting
confidence: 87%
“…NIRS has also been successfully used in a variety of other analytical chemistry applications such as the detection of degradation products in tablets (7); studying drug moisture content over time and water mobility within the drug crystal lattice (8,9); real-time monitoring of moisture during processing using fluidized bed granulation (10,11) or roller compaction (12), measurement of particle size, and size distribution (13)(14)(15); and determining the tablet drug content and content uniformity (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Mayer et al [14] suggested near infrared spectroscopy (NIRS) as an alternative technique to determine the BMP FM . NIRS is widely used in feed and food quality monitoring [19][20][21][22][23][24][25][26] and is accepted since many years as routine method for determining forage quality parameters of various crops. In the bioenergy sector NIRS has been applied to estimate sulphur content in biodiesel [27], for predicting digestibility of maize silage [28][29][30] and fermentation parameters of silages [31], and for the assessment of in situ degradability parameters of crude protein and dry matter characteristics [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its rapidity and nondestructiveness, near-infrared (NIR) spectroscopy is extensively used as a PAT tool to monitor CQAs. For example, during the tableting process, it can be used to monitor tablet hardness, 2,3) tablet porosity, 3) active pharmaceutical ingredient (API) content, 2,[4][5][6] disintegration time, 7) API release rate, 2,8) and pseudo-polymorphs change of API. 9) NIR chemical imaging is also used to examine the distribution of ingredients 10) and the density profile 3,11) on tablet surfaces.…”
mentioning
confidence: 99%